식용달팽이 엑기스 복용에 의한 HIV감염자의 혈중 p24항원농도 감소 - 조영걸; 조군제 (Journal of bacteriology and virology, 1995)
The role of p24 antigen as a surrogate marker has been limited by the presence of high-titer p 24 antibody and antigen-antibody complex in asymptomatic HIV-infected individuals. We used acid treatment method to increase the sensitivity in the detection of p24 antigen in 31 HIV- infected individuals and also it as a tool to evaluate the effect after Achatina fulica Bowdich extract(AFE, 40%) take. The sensitivity by acid treatment in 31 patients increased from 29% to 58%(P<0.001) and absolute level increased 14-fold. Detection rate of p24 in patients with CD4+ T cells less than 100/pl was 100% and then decreased depending to the increase of CD4+ T cells. During the AFE take, p24 antigen decreased in 13 of 18 patients, whereas at 6.2 months from the end of AFE take, it increased in all 16 patients(P<0.001). The p24 antigen level decreased 19% during AFE take, but it increased 98% at 6.2 months from the end of take(P<0.001). These data suggest that acid treatment method increases the detection of p24 antigen and AFE take may inhibit HIV replication in vivo.